Bentuk Ekspresi Emosional Tokoh Utama dalam Kumpulan Cerpen Lelaki-Lelaki Tanpa Perempuan Karya Haruki Murakami: Kajian Psikologi Sastra - Trylestari, Rizky; Muharudin, Eko (RUANG KATA: Journal of Language and Literature Studies, 2023)
Literary works are imaginative creations of authors reflecting upon the social environment of life. Literary works arise from contemplating the meanings and essence of life experienced, felt, witnessed, and expressed. This study examines the forms of emotional expression of the main characters in the "Lelaki-Lelaki Tanpa Perempuan" short story collection by Haruki Murakami. This study aims to describe the forms of emotional expression experienced by the main characters in the "Lelaki-Lelaki Tanpa Perempuan" short story collection by Haruki Murakami. The analysis of the forms of emotional expression of the main characters in the short story collection of "Lelaki-Lelaki Tanpa Perempuan" used a literary psychology approach. Emotional expression is rooted in inner conflict as it pertains to the psyche of an individual. The data for this study consisted of quoted sentences that represent the emotional expression of the main characters in the "Lelaki-Lelaki Tanpa Perempuan" short story collection by Haruki Murakami. A qualitative descriptive method was used to analyze the forms of emotional expression of the main characters. Data collection techniques involved reading and note-taking. Data analysis techniques included data reduction, data presentation, and drawing conclusions. The validity of the data was employed through theoretical triangulation. This study reveals various forms of emotional expression of the main characters in the "Lelaki-Lelaki Tanpa Perempuan" short story collection by Haruki Murakami. These forms of emotional expression include disappointment, resignation, curiosity, worry, anxiety, confusion, fear, and sadness. Keywords: Short Story Collection of "Lelaki-Lelaki Tanpa Perempuan", Emotional Expression, Inner Conflict, Literary Psycholog